An Analysis of Pre-Service Teachers' Lesson Plan - Masfa Maiza (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2019)
Lesson plan is one of the pivotal parts in learning process since it provides the instructions in the classroom. This study deals with the investigation of the aspects of pre-service teachers’ lesson plans based on 2013 Curriculum. It used descriptive qualitative research. As many as ten lesson plans by five pre-service teachers were analysed using document analysis based on theory of Brown (2001) namely goals, objectives, materials and equipment, procedures and evaluation to collect data. The result shows that they are good in creating goals, material and equipment and procedure, but they should improve their ability in creating objectives and evaluation. In short, they are able to design English lesson plans based on its characteristics of 2013 curriculum